2015
DOI: 10.1093/ageing/afv100
|View full text |Cite
|
Sign up to set email alerts
|

A collaborative strategy to improve geriatric medical education

Abstract: The teaching aimed to promote patient-centred care and multidisciplinary collaborative practice, encourage student self-reflection and peer-assisted education and provide insight into the needs of patients with dementia. Student feedback indicated that these objectives had been met. This easily replicable teaching method provides a simple means of improving communication skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…The need for practising communication skills and gaining feedback 53,55 was supported by the use of role play, simulation or 'live' skills practice in seven studies. In one study, 81 simulation was the principal training method, with positive effects on confidence, although their measure was not validated.…”
Section: Teaching Methods Usedmentioning
confidence: 99%
See 3 more Smart Citations
“…The need for practising communication skills and gaining feedback 53,55 was supported by the use of role play, simulation or 'live' skills practice in seven studies. In one study, 81 simulation was the principal training method, with positive effects on confidence, although their measure was not validated.…”
Section: Teaching Methods Usedmentioning
confidence: 99%
“…The systematic review identified a variety of educational and other theories. Two papers gave extensive consideration to educational theories, models and frameworks, 78,81 including the 'learner-centred classroom', Knowles' principles of andragogy, 103 and reflective practice. 144 Beer et al 78 description of specific learning activities with references to a variety of educational theorists, including transformative learning theory 145 and the motivational framework for culturally responsive teaching.…”
Section: Name Of Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…commonly reported by those participants who employed experiential learning activities to teach students about oral health, especially simulation involving a dental professional. Prior research with medical students has demonstrated that students enjoy interactive learning experiences with standardized patients and receiving feedback from clinicians (Cockbain, Thompson, Salisbury, Mitter, & Martos, 2015). Furthermore, simulation is considered an important component of student practical education (Clemmens et al, 2012) and is a popular method for teaching health professions students about oral-systemic health (Djukic et al, 2012;Dolce et al, 2014;Haber et al, 2015).…”
Section: Educational Practicementioning
confidence: 99%